Histopathologic changes in aborted placenta - A Ashour; Nabeia Gheryani; Tunis Meidan (Libyan International Medical University Journal)
Introduction: Histopathological examination of the placenta with clinical implications helps to make the diagnosis and deduce the cause of abortion, fetal mortality, morbidity, and pregnancy complications. Aim: This study aims to determine the frequencies and types of abnormalities of the chorionic villi in the aborted placentae. Materials and Methods: All specimens of products of conception submitted to a private histopathology laboratory in Benghazi during the period (from January 01, 2016 to December 31, 2018) were formalin-fixed, paraffin-embedded, and histopathology reviewed using hematoxylin and eosin stain under light microscopy. The data collected and statistically analyzed using SPSS version 22. Results: The study involved 92 specimens, of which 86 were abnormal and the pathological changes include partial mole (48%), hydropic changes (19%), increased vascularity (chorioangiosis) (13%), fibrosis (10%), numerous Hofbauer macrophages (8%), and abnormal premature calcification (2%). The rest of the specimens (6.5%) were normal placentae. Most of the cases of partial mole (73%) were at the age group of ≥30 years, and cases of abnormal premature calcification were at the age of >40 years. Conclusion: The histopathologic examination is an important tool for diagnosing the placental abnormalities. Most cases of abortion have abnormalities in chorionic villi; the most common abnormality is the partial mole, followed by hydropic change, then increased vascularity (chorioangiosis), fibrosis, and numerous Hofbauer macrophages. Abnormal premature calcification is the least finding. Partial mole occurs at an older age group of ≥30 years.